Cobweb theorems with production lags and price forecasting - Daniel Dufrfesne; Felisa Vázquez-Abad (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
The classical cobweb theorem is extended to include production lags and price forecasts. Price forecasting based on a longer period has a stabilizing effect on prices. Longer production lags do not necessarily lead to unstable prices; very long lags lead to cycles of constant amplitude. The classical cobweb requires elasticity of demand to be greater than that of supply; this is not necessarily the case in a more general setting. Random shocks are also considered.
Keywords: C02; C62; E32; 330